2023
DOI: 10.1186/s12879-023-08481-9
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a clinical predictor for severe manifestation of dengue: a systematic review and meta-analysis

Chao-Ying Chen,
Yu-Yao Chiu,
Yu-Cheng Chen
et al.

Abstract: Background Severe dengue often leads to poor clinical outcomes and high mortality; as a result, it is of vital importance to find prognostic factors associated with the severe form of dengue. Obesity is known to deteriorate many infectious diseases due to impaired immune responses. Several studies have suggested that obese patients with dengue infection tend to have more severe manifestations with poorer prognosis. However, a firm conclusion could not be drawn due to the varied results of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Specifically, we found that obesity was associated with higher odds of presenting fever, headache, and rash in children infected with DENV. Several studies have shown an association between obesity and a higher risk of severe dengue as compared to non-severe dengue [14,15,[35][36][37][38][39][40]. However, we are not aware of reports of the association between obesity and non-severe dengue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we found that obesity was associated with higher odds of presenting fever, headache, and rash in children infected with DENV. Several studies have shown an association between obesity and a higher risk of severe dengue as compared to non-severe dengue [14,15,[35][36][37][38][39][40]. However, we are not aware of reports of the association between obesity and non-severe dengue.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric obesity, whose worldwide prevalence increased 7-fold from 1975 to 2016, has been shown to negatively influence infectious disease outcomes [13]. A meta-analysis of multiple dengue studies revealed that obesity is associated with severe pediatric dengue, though individual reports are mixed [14,15]. Furthermore, greater body surface area and body weight were found to positively correlate with Zika and chikungunya virus infection, respectively [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We showed that when regional poverty increased, the cumulative incidence of SD-DWS reduced by about 7%. Some studies have found that poor nutritional status can be protective against severe disease at the individual level [29,30]. Many host and environmental factors associated with poverty have multiple and complex impacts on dengue virus transmission, requiring detailed and long-term longitudinal research studies.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between obesity and development severe dengue had been observed for many years and reported in children in studies in the 1990s from Thailand, India and El Salvodor [ 23 – 25 ]. Many subsequent studies showed that obesity was an independent risk factor for developing severe dengue in hospitalized patients [ 13 , 14 ] including a recent metanalysis [ 26 ]. However, this is the first study reporting that obesity may also associate with higher rates of hospitalization, which needs further examination with longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%